Uncovering The Secrets: How Profitability, Firm Size, Earnings Management, And Sales Growth Drive Tax Avoidance In Indonesia's Energy Giants (2018-2022) - Purba, Jamian; Sulistyorini Wulandari, Dian; Dayanti, Iis (Journal of International Multidisciplinary Research, 2024)
This study aims to investigate the dynamics of tax avoidance in energy sector companies listed on the Indonesia Stock Exchange during the 2018 to 2022 period, with a focus on the influence of profitability, company size, earnings management, and sales growth. Using a quantitative method, hypothesis testing was conducted based on secondary data collected from the financial statements of energy companies. Through a purposive sampling approach, the analysis included 20 companies, resulting in a dataset consisting of 73 observations. The analysis revealed several interesting findings: profitability did not show a significant effect on tax avoidance, while company size was found to have a significantly positive impact. Meanwhile, earnings management did not significantly contribute to tax avoidance, and sales growth demonstrated a significantly negative relationship with tax avoidance. These findings enrich the understanding of the factors influencing tax strategies in Indonesia's energy